Epidemiology Of Gastrointestinal Nematodiosis In Swamp Buffaloes (Bubalus Bubalis) Of Assam - Hafiz , A.; Rehman , A. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Buffaloes play a major role in the agricultural economy of India. The hot and humid climatic condition of Assam is very congenital for propagation and perpetuation of nematode parasites. Assam has a huge buffalo population, its productivity is low due to many reasons; one of them being gastrointestinal nematodiosis. For better management of these insidious parasitic problems, there is a need to understand the epidemiology of this type of parasite. The present study was envisaged to study the gastrointestinal (G.I.) nematodiosis based on faecal culture and faecal egg count.